Responsividade das versões brasileiras do CPQ11-14 e Child-OIDP - Buzatti, Bruna Cássia Schmidt (2012)
The ability to detect important clinical changes, or responsiveness, is a necessary property of a questionnaire for measure oral health-related quality of life, especially when one wishes to evaluate the effect of clinical therapies to improve the quality of life of patients. However, in Brazil, there are no studies that evaluated the responsiveness of measures destined for adolescents. Aim: The goal of this dissertation is to present a paper of the responsiveness of the Brazilian versions of Child Perceptions Questionnaire (CPQ11-14) and Child Oral Impacts on Daily Performances (Child-OIDP). Material and Methods: Data were collected from a convenience sample of 101 patients of 11-14-year-old attending at adolescent Dental Clinic, Federal University of Santa Maria, Brazil. Subjects answered the CPQ11-14 and the Child-OIDP in two moments: prior to dental treatment and one month later the conclusion of treatment. The responsiveness of CPQ11-14 and Child-OIDP was analyzed through: (I) the mean change observed in scores before and after treatment, (II) an investigation the effect size, (III) an assessment of the statistical significance of within-groups changes over time according to global transition judgement, and (IV) the receiver operating characteristic (ROC) curve, through the sensitivity and specificity of the questionnaires. Results: Positive changes occurred throughout the sample for CPQ11-14 and Child-OIDP. According to global transition judgment, 90.1% of participants reported an improvement following treatment, 7.9% reported no change and 2% reported deterioration. The effect size was 1.0 for the overall CPQ 11-14 and 0.5 for Child-OIDP. In ROC analyses, the area under the curve (AUC) was 0.53 for CPQ11-14 and 0.55 for Child-OIDP. Conclusion: The Brazilian versions of CPQ11-14 and Child-OIDP demonstrated limited responsiveness after dental treatment.